ANALISIS PENGARUH BANK INCOME STRUCTURE TERHADAP RISIKO BANK SYARIAH DI INDONESIA (Studi kasus pada Bank Umum Syariah yang terdaftar di Bursa Efef Indonesia periode 2011-2015) - Yunita, Nurul; Syaichu, Muhamad (Diponegoro Journal of Management, 2017)
The research objective is to analyze influence of independent variables which consist of profit and los sharing (PLS), non profit and loss sharing (NonPLS), and commission and fee (COM) to risk. Selection of sample use purposive sampling method. Purposive sampling method is the method which based on certain criteria. The sample that used in this study are eleven of Islamic bank for period 2011 to 2015. Quantitative data for this study get from Bank Indonesia and monthly financial report of Islamic bank. The data were analyzed by linear regression analysis using SPSS version 16.0 where previously performed classical assumption that includes Normality Test, Multicollinearity Test, Autocorrelation Test and Heterokedastisitas Test with level of significance 5%.The result of t test shows that profit and los sharing (PLS) and non profit and los sharing (NonPLS) have negative and significant influence to risk of Islamic bank. Commission and fee (COM) Â have negative but not significant influence to risk. Based on the result of this count, PLS and non profit and los sharing (NonPLS) variable prove to have negative and significant influence to risk Islamic bank and itâ€™s known that Commission and fee (COM) variable has no effect to risk Islamic bank.